2009
DOI: 10.1007/s00421-009-1033-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic resistance training decreases MuRF-1 and Atrogin-1 gene expression but does not modify Akt, GSK-3β and p70S6K levels in rats

Abstract: Long-term adaptation to resistance training is probably due to the cumulative molecular effects of each exercise session. Therefore, we studied in female Wistar rats the molecular effects of a chronic resistance training regimen (3 months) leading to skeletal muscle hypertrophy in the plantaris muscle. Our results demonstrated that muscle proteolytic genes MuRF-1 and Atrogin-1 were significantly decreased in the exercised group measured 24 h after the last resistance exercise session (41.64 and 61.19%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 44 publications
(50 reference statements)
5
42
0
3
Order By: Relevance
“…The levels of the other genes were not so elevated in the diabetic sedentary group; however the anaerobic training reduced the expression independently on the presence of diabetes, suggesting the positive effect of exercise on the maintenance of the muscle mass, and corroborating for the important and therapeutic role of regular exercise to inhibit the protein breakdown of muscle. In the protocols of chronic anaerobic training for hypertrophy in the experimental animal models, significant reductions in MURF1 e ATROGIN1 in the plantar muscle of healthy, fasted female rats were detected (30). It is known that heterodimers p50/p65 (NFκB) bind to promoter regions of MuRF1 DNA inducing its expression, and, consequently protein de gradation (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of the other genes were not so elevated in the diabetic sedentary group; however the anaerobic training reduced the expression independently on the presence of diabetes, suggesting the positive effect of exercise on the maintenance of the muscle mass, and corroborating for the important and therapeutic role of regular exercise to inhibit the protein breakdown of muscle. In the protocols of chronic anaerobic training for hypertrophy in the experimental animal models, significant reductions in MURF1 e ATROGIN1 in the plantar muscle of healthy, fasted female rats were detected (30). It is known that heterodimers p50/p65 (NFκB) bind to promoter regions of MuRF1 DNA inducing its expression, and, consequently protein de gradation (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…2015;59/5 tion in the cells, returning to basal levels in 24 hours (30). In the present study the sacrifice and removal of tissues were performed after 24 hours of the end of the sixweek anaerobic training.…”
Section: Anaerobic Training Avoids Proteolysismentioning
confidence: 93%
“…This evaluation should be performed in both healthy and atrophic conditions. Recently, our group demonstrated that a chronic low-frequency, low-volume, and high-intensity RE regime in energy-restricted animals promoted significant muscle remodeling (hypertrophy) (6). Since muscle disuse can be easily counteracted by body weight overload (13), it is supposed that a low-frequency and low-volume RE protocol may be effective in restoring muscle mass.…”
Section: Resistance Exercise Variables Volume and Frequencymentioning
confidence: 99%
“…The morphological and functional adaptations to resistance exercise (RE) have been well described, among them the positive responses of the neuromuscular system (neural adaptations) (1,2), muscle architecture (angle of pennation), biochemical composition (myosin heavy chain (MHC) isoform transition) (3,4), and the accumulation of myofibrillar proteins (5,6). These responses may occur according to the nature of the stimulus applied (i.e., the variables of the training program).…”
Section: Introductionmentioning
confidence: 99%
“…Karagounis et al investigated the effects of three bouts of resistance exercise on TNF-α and IKK using a rat training model, and showed that the expression of these proteins markedly increased in response to the initial bout, whereas the responses to subsequent bouts of exercise declined gradually 79) . Zanchi et al also showed that a 12-wk resistance training period caused decreases in atrogin-1 and MuRF1 in rats 80) . These studies suggest that repeated bouts of resistance exercise diminish the acute increase in MPB after exercise.…”
Section: -2 Cell Signaling In Muscle Protein Breakdownmentioning
confidence: 99%